Autonomy and Responsibility in Self-Directed Learning: A Correlational Study on Students’ Learning Motivation - Falah Aulia Sani; Uswatun Khasanah; Zahra Rahmatika; Baharudin Baharudin (MAN 4 Kota Pekanbaru, 2025)
This study aims to examine the relationship between learning motivation and learning autonomy in Fiqh learning at Al Hikmah Islamic Boarding School, Bandar Lampung. A quantitative correlational design was employed. The sample consisted of 32 third-grade Wustho students, representing the entire population (N = 32). Data were collected using validated and reliable Likert-scale questionnaires and analyzed using Pearson correlation. The results revealed a very weak correlation between learning motivation and learning autonomy (R = 0.030), with a coefficient of determination of R² = 0.001. The significance test yielded a Sig. value of 0.873 (> 0.05), indicating that the relationship between the two variables is not statistically significant. These findings suggest that learning motivation explains only a negligible proportion of the variance in students’ learning autonomy within the context of Fiqh learning in a pesantren environment.